Studies on pyrrolidinones. Reaction of pyroglutamic acid and vinylogues with aromatics in Eaton’s reagent - Ghinet, Alina; Van Hijfte, Nathalie; Gautret, Philippe; Rigo, Benoît; Oulyadi, Hassan; Rousseau, Jolanta (Tetrahedron, 2012)
The optimization of the synthesis of 5-aryl-2-pyrrolidinones through decarbonylation of pyroglutamic acid in Eaton’s reagent, in presence of aromatic derivatives, is described. The utilization of these reaction conditions in the arylation of enaminoester vinylogues ( 17, 24) of pyroglutamic acid was also realized, confirming that these derivatives are subject to decarbonylationî in the same way as the parent acid. Depending on the nature of the aromatic derivative ( 15, 21, 28, and 32), two different families of compounds were obtained. Many by-products were also formed, suggesting a utilization of this reaction for compounds more stable than the enaminoesters and enaminonitriles used in this study. The possibility of enaminoesters reacting with aromatics in bimolecular reactions to give enaminoketones should also be noted. Five synthesized compounds were evaluated for their antiproliferative activity on the NCI-60 cancer cell lines panel. [Display omitted]